A unique "fishtail-like" four-way shape memory effect of compositionally graded NiTi. (15th January 2017) - Meng, Qinglin; Wu, Zhigang; Bakhtiari, Reza; Shariat, Bashir S.; Yang, Hong; Liu, Yinong; Nam, Tae-hyun
Abstract: This paper reports a complex four-way shape memory effect of a compositionally graded NiTi thin plate. The composition gradient is created by surface diffusion of Ni into the plate. After a 15% tensile deformation pre-treatment, the compositionally graded plate exhibits a complex four-way shape memory effect in bending mode, by which the metal exhibits a back-and-forth shape change upon a complete thermal cycle. This is analogous to a "fishtail-like" motion, resulting from the sequential transformation through the thickness of the plate as dictated by Ni content gradient. Such "four-way" shape memory effect has not been achieved in NiTi alloys before. Graphical abstract: Complex "4-way" shape memory behaviour of a compositionally graded NiTi thin strip after 15% of tensile deformation. In this figure, the sample bends towards one direction (increase of curvature) initially and then bends backwards (decrease of curvature) upon one cooling (the blue curve). The same process repeats also during heating, thus exhibiting shape change in four directions within one complete thermal cycle.